PENERAPAN PRINSIP GOOD GOVERNANCE DALAM PENGELOLAAN IT CENTER DI DINAS BINA MARGA KABUPATEN KOTABARU - Sifa Fauziah (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2019)
The purpose of the study is to know the application of good governance principle in managing the IT Center at Bina Marga Department Kotabaru regency.  The researcher used descriptive  qualitative research  as the method of the study. From the result of the research, the researcher found that the application of Good Governance principle in managing IT Center at Bina Marga Department Kotabaru Regency was measured as well by using 9 principles, such as   participation   indicator,  law  indicator,  transparency  indicator,  responsive indicator,  consensus  indicator, equilavment indicator, effectivity and efficiency indicator,           accountability  indicator,  and  visibility  indicator.  Lack  of  internet network and the minimum socialization  occurred to be the obstacle factors in delivering the information. For the supporting factors, the researcher found human resource and information data became the supporting factors in  managing IT center well.